Патогенетические особенности метаболизма клеток крови при различном течении язвенной болезни у человека - Борзенко, Б.Г.; Бакурова, Е.М.; Миронова, К.А.; Жебеленко, Я.Г.; Богатырева, Е.В. (Таврический медико-биологический вестник, 2012)
Вивчено порівняльну активність ферментів метаболізму попередників ДНК: ТК, ТФ, АДА у
сироватці крові, лімфоцитах і тромбоцитах здорових людей і хворих на ВХ та РШ різного віку. Активність
ТФ при ВХ знаходиться у межах норми у хворих у виці до 40 років, а далі різко знижується, як у всіх
пацієнтів при РШ. Виявлено підвищення активності ТК, АДА в сироватці крові при ВХ та РШ. Активність
АДА знижена в лімфоцитах, що супроводжується зниженням їх функціональної готовності. Підвищення
цього фермента в тромбоцитах сприяє утворенню їх агрегатів, посилюючих ішемію слизової оболонки
шлунка або навпаки зміна активності ферментів при ВХ у хворих у віці 46-60 років, подібно зміні при
РШ, може сприяти малігнізації виразки. Comparative activity of DNA precursor‘s metabolism enzymes (TK, TP, ADA) was studied in blood serum,
lymphocytes and platelets of healthy people and patients with ulcer disease and gastric cancer TK and ADA
activity in blood serum was revealed in patients with ulcer disease and gastric cancer. Unfortunatly, decreased
ADA activity in lymphocytes is accompanied by a decrease in their functional deficiency and immune system
decline. Increased activity of this enzyme in platelets contributes to the formation of aggregates, promoting
ischemia of the gastric mucosa. Interestingly, TP activity is within normal range in younger patients (aged
fewer than 40) with ulcer disease while sharply decreases after 46-60 years similarly as in patients of the
same age with stomach cancer. In light of this study, we could assume that similar changes in enzyme activity
both in patients with ulcer disease and gastric cancer aged 46-60 years can contribute to ulcer malignantion
and are a factor of oncological risk.